Transcatheter mitral and tricuspid interventions—the bigger picture: valvular disease as part of heart failure - Curio, Jonathan; Beneduce, Alessandro; Giannini, Francesco (Frontiers in Cardiovascular Medicine, 2023)
The prevalence of mitral (MR) and tricuspid regurgitation (TR), especially in heart failure (HF) populations, is high. However, the distinct role of atrioventricular valve diseases in HF, whether they are merely indicators of disease status or rather independent contributors in a vicious disease cycle, is still not fully understood. For decades, tricuspid regurgitation (TR) was considered an innocent bystander subsequent to other heart or lung pathologies, thus, not needing dedicated treatment. Recent increasing awareness towards the role of atrioventricular valve diseases has revealed that MR and TR are, in fact, independent predictors of outcome in HF, thus, warranting attention in the HF treatment algorithm. This awareness arose, especially, with the development of minimally invasive transcatheter solutions providing new treatment options, which can also be used for patients considered as having increased surgical risk. However, outcomes of such transcatheter treatments have, in part, been sub-optimal and likely influenced by the status of the concomitant HF disease. Thus, this review aims to summarize data on the current understanding regarding the role of MR and TR in HF, how HF impacts outcomes of transcatheter MR and TR interventions, and how the understanding of this relationship might help to identify patients that benefit most from these therapies, which have proven to be lifesaving in properly selected candidates.